Physiological and genotoxic effects of Molybdenum-induced copper deficiency in cattle - Picco, Sebastian Julio (2012)
Molybdenosis is a disease caused by the depressing effect of molybdenumn (Mo) on the physiological availability of Cu. The present study was carried out in order to analyze the ability of Mo to cause damage on the DNA integrity and changes in membrane fatty acids by oxidative damage. Holstein male calves were fed a Mo-supplemented diet for 9 months. Variables evaluated were plasma Cu concentration, erythrocyte Cu content and SOD activity, comet assay and analysis of the fatty acid composition of erythrocyte membranes. The statistical design was a completely randomized with one single factor and two replications. Copper plasma concentration, erythrocyte copper concentration and Cu/Zn SOD activity were analyzed using the t test. Chi-square test was used to compare the number of cells with DNA damage and one-way analysis of variance and Tukey test (p£0.05) for fatty acid composition and lipid peroxidation. Results showed that Mo in the diet induced a depletion of hepatic Cu storage, a decrease of Cu plasma and erythrocyte levels, a fall in Cu/Zn-SOD activity, changes in membrane fatty acids composition and DNA damage. These results are in agreement with the three phases model of copper deficiency and validate the occurrence of molybdenosis or secondary hypocuprosis. Further studies will be necessary to explore the mechanisms involved in the DNA damage and to distinguish primary molybdenum toxicosis from the molybdenum-induced copper deficiency.